SOSIALISASI DIGITAL GUNA MENGARAHKAN SISWA/SISWI SMPN 2 GUNUNG SINDUR UNTUK PEMANFAATAN INTERNET PRODUKTIF - Asyiah, Nilovar; Rahayu, Eka Sri; Nurhasanah (Abdi Jurnal Publikasi, 2024)
The utilization of the internet among teenagers nowadays tends to lean towards less productive activities such as playing online games, social media, and excessive consumption of entertainment content. This can disrupt their academic and social development. Therefore, systematic efforts are needed to guide internet use towards more productive activities. This program aims to raise awareness and improve the skills of students at SMPN 2 Gunung Sindur in utilizing the internet as a learning tool, developing creativity, and exploring opportunities that can support their future.The introduction to internet technology and platforms considers other important aspects such as online safety, privacy, digital ethics, and the development of critical skills. This program provides students with an understanding of wise and productive internet use. Additionally, students will gain an understanding of internet usage ethics and ways to avoid negative risks such as cyberbullying and false information.Students at SMPN 2 Gunung Sindur will be able to utilize the internet more productively and responsibly, enhancing digital skills beneficial for their academic and personal development in the future. The success of this program is measured by the increase in students' knowledge and skills in utilizing the internet, as well as behavioral changes towards more positive and constructive internet use.